SUCCOR study: an international European cohort observational study comparing minimally invasive surgery versus open abdominal radical hysterectomy in patients with stage IB1 cervical cancer. Issue 9 (11th August 2020) - Chiva, Luis; Zanagnolo, Vanna; Querleu, Denis; Martin-Calvo, Nerea; Arévalo-Serrano, Juan; Căpîlna, Mihai Emil; Fagotti, Anna; Kucukmetin, Ali; Mom, Constantijne; Chakalova, Galina; Aliyev, Shamistan; Malzoni, Mario; et al.
Abstract : Background: Minimally invasive surgery in cervical cancer has demonstrated in recent publications worse outcomes than open surgery. The primary objective of the SUCCOR study, a European, multicenter, retrospective, observational cohort study was to evaluate disease-free survival in patients with stage IB1 (FIGO 2009) cervical cancer undergoing open vs minimally invasive radical hysterectomy. As a secondary objective, we aimed to investigate the association between protective surgical maneuvers and the risk of relapse. Methods: We obtained data from 1272 patients that underwent a radical hysterectomy by open or minimally invasive surgery for stage IB1 cervical cancer (FIGO 2009) from January 2013 to December 2014. After applying all the inclusion-exclusion criteria, we used an inverse probability weighting to construct a weighted cohort of 693 patients to compare outcomes (minimally invasive surgery vs open). The first endpoint compared disease-free survival at 4.5 years in both groups. Secondary endpoints compared overall survival among groups and the impact of the use of a uterine manipulator and protective closure of the colpotomy over the tumor in the minimally invasive surgery group. Results: Mean age was 48.3 years (range; 23–83) while the mean BMI was 25.7 kg/m 2 (range; 15–49). The risk of recurrence for patients who underwent minimally invasive surgery was twice as high as that in the open surgery group (HR, 2.07; 95% CI, 1.35 to 3.15; P=0.001). Similarly, the risk of death was 2.42-times higher than in the open surgery group (HR, 2.45; 95% CI, 1.30 to 4.60, P=0.005). Patients that underwent minimally invasive surgery using a uterine manipulator had a 2.76-times higher hazard of relapse (HR, 2.76; 95% CI, 1.75 to 4.33; P<0.001) and those without the use of a uterine manipulator had similar disease-free-survival to the open surgery group (HR, 1.58; 95% CI, 0.79 to 3.15; P=0.20). Moreover, patients that underwent minimally invasive surgery with protective vaginal closure had similar rates of relapse to those who underwent open surgery (HR, 0.63; 95% CI, 0.15 to 2.59; P<0.52). Conclusions: Minimally invasive surgery in cervical cancer increased the risk of relapse and death compared with open surgery. In this study, avoiding the uterine manipulator and using maneuvers to avoid tumor spread at the time of colpotomy in minimally invasive surgery was associated with similar outcomes to open surgery. Further prospective studies are warranted.